Presidential elections, divided politics, and happiness in the USA - Pinto, S. (2022)
We examine the effects of the 2016 and 2012 US presidential election outcomes on subjective wellbeing across party identification. We use Gallup data and a regression discontinuity approach, and focus primarily on evaluative (life satisfaction) and hedonic (positive and negative affect) indicators. We find that both elections had strong negative wellbeing effects on those who identified with the losing party, with little or no increase in wellbeing for those identifying with the winning party. The negative effects for the losing side were larger in 2016 than in 2012, by a factor of three on some indicators, and were driven mainly by women and middle-income households. As such, both elections had a net negative wellbeing effect, but more so in 2016. Local voting patterns did not have a substantial wellbeing impact, nor did congressional elections taking place the same day. In 2016, the election also changed respondents’ perceptions about the economy, their financial status, and their community. After both elections, hedonic wellbeing gaps across parties typically dissipated within two weeks, but there was more persistence in evaluative wellbeing gaps, especially in expected life satisfaction. The latter gap persisted throughout 2017.